Analysis of the chemoprophylactic effect on close contacts of patients with active tuberculosis and positive tuberculin skin tests. Issue 3 (1st September 2014) - Lin, Cunzhi; Wang, Fangfang; Li, Jinfeng; Du, Jianxin; Wang, Hairong; Zhu, Xinhong
Abstract : Objective: The current study analyzed the chemoprophylactic effect of isoniazide on close contacts of patients with active tuberculosis and positive tuberculin skin tests (TSTs). Methods: A total of 1206 close contacts of patients with active tuberculosis and strongly-positive TSTs were enrolled. The patients had chest X-ray examinations. Patients without tuberculosis and other diseases were divided into the following groups: 90 patients in the prophylaxis group, who were given 300 mg of isoniazid qd (3–5 mg/kg for children) over a 10-month treatment course; and 89 patients in the control group without drug therapy. Both groups were followed for 10 years. Results: (1) There were 568 patients with negative results and 638 with positive results, including 445 with ordinarily- and moderately-positive results, and 193 with strongly-positive results (a positive rate of 52.9% [638/1206] and a strongly-positive rate of 16.0% [193/1206]). Fourteen tuberculosis patients were identified (tuberculosis detection rate of 1.1%). (2) During the 3-year period of follow-up, there were 4 patients in the prophylaxis group and 12 patients in the control group who acquired tuberculosis (a morbidity rate of 4.7% [4/84] and 13.4% [12/89], respectively), and the difference was statistically significant (χ 2 =3.916, P =0.048). Six patients in the prophylaxis group, all of whom were children, discontinued medication use during the course of treatment due to adverse drug reactions, for an adverse drug reaction occurrence rate of 6.6% (6/90), a medication completion rate of 93.3% (84/90), and a 3-year protection ratio of 64.6%. (3) During the 4–6 year period, there were two patients in the prophylaxis group and three patients in the control group who acquired tuberculosis (a morbidity rate of 2.5% [2/78] and 4.1% [3/73], respectively), two in the prophylaxis group and four in the control group who were lost to follow-up (a loss to follow-up rate of 2.5% [2/80] and 5.1% [4/77], respectively), and the difference was not statistically significant (χ 2 =0.006, P =0.940; χ 2 =0.215, P =0.643). (4) During the 7–10 year study, there was one patient in the prophylaxis group and two patients in the control group who acquired tuberculosis (a morbidity rate of 1.3% [1/72] and 3.1% [2/64], respectively), and four in the prophylaxis group and six in the control group who were lost to follow-up (a loss to follow-up rate of 5.2% [4/76] and 8.5% [6/70], respectively), and the difference was not statistically different (χ 2 =0.011, P =0.918; χ 2 =0.176, P =0.675). (5) Within 10 years, there were 7 patients in the prophylaxis group and 17 patients in the control group who acquired tuberculosis (a morbidity rate of 8.3% [7/84] and 21.5% [17/79], respectively; χ 2 =4.770, P =0.029), and 6 in the prophylaxis group and 10 in the control group were lost to follow-up (the loss to follow-up rate was 7.1% [6/84] and 11.2% [10/89], respectively; χ 2 =0.863, P =0.353). Conclusion: Close contacts of patients with active tuberculosis are at high-risk for acquiring tuberculosis. It is safe and effective for patients with strongly-positive TST results to undergo isoniazid chemoprophylaxis for 10 months.